2013
DOI: 10.1371/journal.pone.0081101
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Mimics Estrogen-Driven Cell Proliferation and Prolactin Secretion from Anterior Pituitary Cells

Abstract: Cadmium (Cd) is a heavy metal of considerable occupational and environmental concern affecting wildlife and human health. Recent studies indicate that Cd, like other heavy metals, can mimic effects of 17β-estradiol (E2) involving E2 receptor (ER) activation. Lactotrophs, the most abundant cell type in anterior pituitary gland, are the main target of E2, which stimulates cell proliferation and increases prolactin secretion through ERα. The aim of this work was to examine whether Cd at nanomolar concentrations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
(63 reference statements)
2
34
0
Order By: Relevance
“…Here, we demonstrated that both toxicants stimulate cell proliferation, modify pituitary hormone secretion, and up-regulate E2-responsive genes. Our present data tally with previous results from our laboratory demonstrating that nanomolar Cd concentrations exert estrogenic activity in the anterior pituitary cells in culture and in lactosomatotroph GH3 cell line (Ronchetti et al 2013). Regarding iAs, its xenoestrogenic effects on this gland have not been reported yet.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we demonstrated that both toxicants stimulate cell proliferation, modify pituitary hormone secretion, and up-regulate E2-responsive genes. Our present data tally with previous results from our laboratory demonstrating that nanomolar Cd concentrations exert estrogenic activity in the anterior pituitary cells in culture and in lactosomatotroph GH3 cell line (Ronchetti et al 2013). Regarding iAs, its xenoestrogenic effects on this gland have not been reported yet.…”
Section: Discussionsupporting
confidence: 89%
“…Cd and iAs, at micromolar doses, have been shown to inhibit anterior pituitary secretion through feedback mechanisms or by directly affecting anterior pituitary cells (Lafuente & Esquifino 1999, Poliandri et al 2003, 2006, Sarkar et al 2003, Miler et al 2010, Ronchetti 2014. However, we previously showed that Cd at nanomolar concentrations exerts E2-like activities on these cells in culture (Ronchetti et al 2013). However, to date, iAs-mediated effects on the anterior pituitary gland have not been studied.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, the estrogen receptor is involved also in stimulation of proliferation and transcription in pituitary cell lines [14, 36, 39, 45], mainly via the ERK pathway [16]. Current evidence demonstrates that disruptors call several additional pathways into play including the AhR–AIP–ARNT system [23].…”
Section: Discussionmentioning
confidence: 99%
“…The toxicological evidence with respect to cadmium’s effects on the reproductive system was recently reviewed [1214]. Cadmium may interfere with hormonal functioning by binding at both the nuclear estrogen receptor [15] and G-protein coupled receptor 30 (GPR30) [1618] and indirectly by P450 side-chain cleavage or through the low density lipoprotein receptor [19, 20] thus, cadmium may also be involved in the etiology of hormonally sensitive health outcomes and diseases. Experimentally, cadmium has shown effects on estrogenic activity [15, 2124], including toxic effects to the ovary [21, 2527].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, cadmium has shown effects on estrogenic activity [15, 2124], including toxic effects to the ovary [21, 2527]. Together with estrogen, cadmium increased estrogen receptor alpha mRNA expression beyond either estrogen or cadmium alone [20]. Further, cadmium may contribute to disease processes by altering the balance of oxidative stress [28].…”
Section: Introductionmentioning
confidence: 99%